Disregarding population specificity: its influence on the sex assessment methods from the tibia - Kotěrová, Anežka; Velemínská, Jana; Dupej, Ján; Brzobohatá, Hana; Pilný, Aleš; Brůžek, Jaroslav (International journal of legal medicine, 2017)
Forensic anthropology has developed classification techniques for sex estimation of unknown skeletal remains, for example population-specific discriminant function analyses. These methods were designed for populations that lived mostly in the late nineteenth and twentieth centuries. Their level of reliability or misclassification is important for practical use in today's forensic practice; it is, however, unknown. We addressed the question of what the likelihood of errors would be if population specificity of discriminant functions of the tibia were disregarded. Moreover, five classification functions in a Czech sample were proposed (accuracies 82.1-87.5 %, sex bias ranged from -1.3 to -5.4 %). We measured ten variables traditionally used for sex assessment of the tibia on a sample of 30 male and 26 female models from recent Czech population. To estimate the classification accuracy and error (misclassification) rates ignoring population specificity, we selected published classification functions of tibia for the Portuguese, south European, and the North American populations. These functions were applied on the dimensions of the Czech population. Comparing the classification success of the reference and the tested Czech sample showed that females from Czech population were significantly overestimated and mostly misclassified as males. Overall accuracy of sex assessment significantly decreased (53.6-69.7 %), sex bias -29.4-100 %, which is most probably caused by secular trend and the generally high variability of body size. Results indicate that the discriminant functions, developed for skeletal series representing geographically and chronologically diverse populations, are not applicable in current forensic investigations. Finally, implications and recommendations for future research are discussed.
Keywords: Forensic Anthropology; Anatomic Landmarks; soudní antropologie; anatomická značka; Humans; GAME method; lidé středního věku; neuronové sítě; Female; Aged; dospělí; Sex Determination by Skeleton; Forensic anthropology population data; Neural Networks, Computer; senioři; lidé; určení pohlaví podle kostry; Population specificity; Adult; ženské pohlaví; Male; Middle Aged; Sex determination; tibie; Aged, 80 and over; diskriminační analýza; senioři nad 80 let; Discriminant function analysis; Discriminant Analysis; mužské pohlaví; Tibia